A prospective comparative study of intravesical chemotherapy versus immunotherapy in non-muscle invasive bladder cancer - Mishra, Shatakshi; Kumar, Vinay (International Surgery Journal, 2025)
Background: Non-muscle invasive bladder cancer (NMIBC) constitutes a significant proportion of urothelial malignancies. The optimal choice between intravesical chemotherapy and immunotherapy remains debatable, particularly regarding efficacy and recurrence rates. To prospectively compare the efficacy of intravesical chemotherapy and immunotherapy in NMIBC patients in terms of recurrence, progression, and therapy-related complications. Methods: A randomized controlled trial was conducted on 56 NMIBC patients from March 2023 to March 2025 at GSVM Medical College, Kanpur. Patients were assigned to either intravesical chemotherapy (Arm A: Gemcitabine/Mitomycin C) or immunotherapy (Arm B: Bacillus Calmette-Guérin–BCG). They were followed for 9 months with regular cystoscopic evaluation. Clinical outcomes including recurrence and complications were analyzed. Results: Recurrence was significantly lower in the immunotherapy group compared to chemotherapy (p<0.001). Histological subtype and tumor stage correlated with recurrence. Most recurrences occurred after 9 months. The immunotherapy group also showed a higher rate of bladder irritation and LUTS. Conclusion: Intravesical BCG immunotherapy is superior in reducing recurrence compared to chemotherapy in NMIBC, although it is associated with increased local side effects. Larger, multicenter studies with extended follow-up are warranted.